Mídias sociais promovendo lealdade: um estudo do twitter na interação entre clientes e empresa - Tótoli, Flávia do Nascimento (2012)
The present study investigated whether the use of social media, particularly Twitter promote customer loyalty to the company. To that end, we organized a theoretical construct, which showed the chain of concepts based on the literature reviewed. In order to examine the consistency of the proposed relationship, this research determined as a methodology, a triangulation of qualitative and quantitative research. The first phase was the completion of a survey that examined the issue of customer loyalty to Twitter. Then, we carried out a desk research, in which were gathered and analyzed the contents of the Twitter profiles of selected companies (Microsoft, Intel, Google and IBM). The expected result for this field research was the confirmation of the theoretical construct. The contribution that produced this dissertation was to develop a model of loyalty, based on the use of Twitter. Initially we present the first chapter with an introduction to research the problem, the goal, s assumptions and reasoning behind the study. The second chapter is to review theoretical, which are presented in the following variables: social media, interactivity, relationship and loyalty, concluding with the presentation of a theoretical construct developed based on literature gathered. The third chapter describes the methodology chosen, in a triangulation for the survey field. Presented the rationale of the study and epistemological choices made ​​by the author. The fourth chapter shows the analysis and interpretation of quantitative research and qualitative. Next, the fifth chapter presents the conclusions and the sixth chapter presents the research limitations and suggestions for advancing the same.